Peran Komite Sekolah Dalam Peningkatan Mutu Pendidikan Madrasah - Ramli Ramli (Master's degree Department of Islamic Education Postgraduate Program of Universitas Islam Negeri (State Islamic University) Ar-Raniry, Banda Aceh in cooperation with Center for Research and Community Service (LP2M), 2021)
One form of actualization in Indonesian education was the establishment of a body called School Committee that replaced the existence of the Education Organizing Body (BP3), stipulated through the Decree of the Minister of National Education No. 044/U/2002 dated April l2, 2002. The name of BP3 was changed to the School Committee due to the need for full community involvement in improving the quality of education. One of the objectives of the school committee is to increase the responsibility and participation of the community in the implementation of education in the education unit. In this present study, the focuses were on the process and the mechanism of the formation of the madrasah (Islamic school) committee organization, the planning carried out by the madrasah committee in improving the quality of madrasah education, and the implementation of the madrasah committee programs in improving the quality of education in Aceh Besar District. This study employed qualitative research methods. Data were collected through observation, interviews, and documentation. Findings showed that the process and the mechanism in forming the madrasah committee in Aceh Besar District were based on the decision of the Ministry of Education on the establishment of community-based organizations, including by mutual deliberations or meetings held every 3 years in a transparent, accountable, and democratic manner, and by involving the community as an education unit partner. Further, the planning of the madrasah committee in improving the quality of madrasah education was carried out by establishing the structure of the committee and holding regular meetings with madrasahs and the community every three months or at the end of each semester, and also by preparing and organizing religious and national holidays together with other madrasahs. In addition, the madrasah committee programs were well implemented in Aceh Besar, as seen from the involvement of all elements from both madrasahs as the organizers of the activities and the community as the provider of advice and input. The programs included the religious and extracurricular programs in collaboration with the sub-districts and district of Aceh Besar.